Analysis of Degradation Mechanisms in LiNi0.8Mn0.1Co0.1O2 Lithium-ion Battery Cathodes During High-Rate Charge–Discharge Cycling - Daisuke SHIBATA; Rinka YAMAMOTO; Mao MATSUMOTO; Haruno MURAYAMA; Chengchao ZHONG; Keiji SHIMODA; Ken-ichi OKAZAKI; Shohei YAMASHITA; Yuki ORIKASA (Electrochemistry)
The increasing demand for cobalt reduction and high energy density in lithium-ion batteries has accelerated the development of cathode-active materials based on Ni-rich layered oxides. However, Ni-rich cathodes, such as LiNi0.8Mn0.1Co0.1O2 (NMC811), suffer from capacity degradation due to factors including crystal structure changes, particle fractures, and the formation of surface resistive layers. While these degradation mechanisms have been extensively studied, the specific effects of high current density on capacity fading remains unclear. In this study, we investigate the degradation mechanisms of NMC811 cathodes cycled at 0.1C and 2C rates. Cycling at 2C rate results in severe capacity fading over 50 cycles. Synchrotron X-ray diffraction confirms the preservation of the crystal structure without evidence of Li–Ni site exchange. X-ray computed tomography reveals surface breakdown of primary particles following high-rate cycling. X-ray absorption spectroscopy and hard X-ray photoelectron spectroscopy indicate the formation of a thick resistive surface layer after the cycling at 2C rate. This layer, formed due to high polarization and intensified side reactions, impedes lithium-ion transport, leading to significant capacity degradation.